Class size, grouping practices and classroom management. (2019) - Blatchford, Peter; Russell, Anthony
Highlights: Understanding of class size effects on classroom processes is very thin. Results indicate that class size does not directly impact on attainment. Class size affects classroom groups, management and teaching. Need to think strategically about teaching groups and group work. A 'social pedagogical' approach is proposed. Abstract: The intense argument over class size has been about associations with pupil academic outcomes. Often overlooked is the way class size affects teachers' classroom management of learning in groups. As part of a large scale multi-method project that tracked pupils' educational progress from 5 to 11 years, data were collected on teachers' experiences through annually administered questionnaires at Y4, 5 and 6 (n = 486) and interviews with teachers as part of detailed case studies (n = 10 schools). Results show that class size does not directly impact on attainment, but works through the many ongoing difficult decisions teachers have to make about how best to manage and teach pupils in groups. A strategic approach is needed to teaching groups and collaborative learning in groups.